2013
DOI: 10.1021/op300342y
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Manufacturing Route to PF-610355 (2): Synthesis of the API

Abstract: PF-610355 is a novel inhaled β-2 adrenoreceptor agonist. Process development of the final intermediate and the API are discussed with emphasis on the control of physical properties and subsequent isolations. This includes development of a constant volume distillation and evaluation of Nutsche filtration, agitated filter drying, and centrifugation to prevent particle attrition. The optimized process employed to manufacture 100 kg of the API is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Several more case studies of the successful use of functionalized silicas and resins have been reported by pharmaceutical companies, demonstrating their utility and applicability on an industrial scale. An additional benefit exhibited by functionalized silica scavengers is the ease of metal recovery via incineration. This is a favorable property, as metal catalysts typically account for approximately 5–20% of total manufacturing costs; hence, recovery and potential recycling of the metal are highly beneficial in making the process as economical as possible .…”
Section: Adsorptionmentioning
confidence: 99%
“…Several more case studies of the successful use of functionalized silicas and resins have been reported by pharmaceutical companies, demonstrating their utility and applicability on an industrial scale. An additional benefit exhibited by functionalized silica scavengers is the ease of metal recovery via incineration. This is a favorable property, as metal catalysts typically account for approximately 5–20% of total manufacturing costs; hence, recovery and potential recycling of the metal are highly beneficial in making the process as economical as possible .…”
Section: Adsorptionmentioning
confidence: 99%
“…Alternatively, trace metals may be quantified by fluorometric or colorimetric methods that are more amenable to on-site operation . Palladium is a scarce but useful metal due to its high catalytic turnover numbers in many chemical reactions. , After palladium-catalyzed reactions are employed in pharmaceutical production, extensive purification must be employed to remove residual palladium, requiring analysis of trace palladium. Current instrumentally intensive methods take a significant amount of time, on the order of days or even weeks, including transportation of samples, to quantify residual palladium, hindering progress during the purification process . To expedite this process, many groups have reported fluorometric or colorimetric methods to detect palladium, , some of which rely on the palladium(0)-catalyzed cleavage of an allylic C–O bond. …”
mentioning
confidence: 99%